LOW COST TECHNOLOGY FOR THE DEVELOPMENT OF COCONUT SMALLHOLDINGS - DR. D. V. LIYANAGE (International Coconut Community Journal, 1986)
The management practices recommended to increase coconut production in smallholdings are largely based on a seed‑fertilizeragrocide technology. The goal is to maximise production. HigI yielding varieties that need high inputs and management lavel, have been introduced. Application of chemical fertilizers pesticides and weedicides are advocated. The smallholders with limited funds at their disposal and faced with other constraints are unable to purchase the inputs. Thus an inappropriate technology is being passed on to them.